PENGETAHUAN TANAMAN OBAT TRADISIONAL UNTUK PENYAKIT ANAK PADA KOMUNITAS REMAJA DI BALI : SEBUAH KAJIAN EKOLINGUISTIK - Rasna, I Wayan (Bumi Lestari; Vol 13 No 1 (2013), 2013)
Abstract This study aims at knowing: 1) the level of young generations’ knowledge about the use of traditional medical plantation for curing children’s diseases; and 2) the implication of the aims 1 above to Eco linguistics. This study took place in the province of Bali, consisting of 8 regencies and one city government. The total samples of the study were 225 young generations’ and 45 spiritual people. The samples of the study were determined by using purposive quota sampling. The data related to the young generations’ knowledge were collected through test. The data as to the implication of aims 1 were gathered by means of interview. The result of the study shows that: 1) the Balinese young generations’ knowledge about the use of traditional medical plantation is 48.4% (not enough); and 2) the young generations having better knowledge and will be more familiar with the terms of medical plantation, such as the young generations in Karangasem with the percentage of 73.12% (good), the young generations in Klungkung 70.50% (good), and Bangli 71.36% (good). They are a bit more familiar with medical plantation terms. Referring to the result of the study, it is suggested to socialize about the usefulness of medical plantation, the improvement of the skill in producing medicine from medical plantation, and synergizing the related components to lexical maintenance and environment.
Keywords: Key Words: maintenance; lexical; medical plantation; ecolinguistics.